Influence of Service Quality, Price, and Location on Customer Satisfaction: A Case Study of Snackdaily, a Garut Specialty Food in Medan - Audini, Vira; Nasution, Annio Indah Lestari; Atika, Atika (Jurnal Manajemen Bisnis, 2024)
This study examines the level of customer satisfaction and the influencing factors within the context of customer choices regarding Snackkdaily, a revitalized traditional Garut dish in Medan. Utilizing a quantitative research method, data was collected from 96 respondents through sampling procedures and questionnaires. Multiple regression analysis was employed to analyze the data. The findings indicate that location, price, and service quality significantly influence customer satisfaction levels towards Snackkdaily in Medan. Additionally, aspects related to service quality and price factors also impact customer satisfaction. Specific location characteristics also play a role in enhancing customer satisfaction towards Snackkdaily as a rebranded Garut specialty food in Medan. This research holds practical urgency for business stakeholders and decision-makers. By understanding consumer preferences and needs, food business owners such as Snackkdaily can enhance their marketing strategies, services, and locations to maintain and improve customer satisfaction. Moreover, this study offers valuable insights for the local business community in identifying untapped market opportunities and enhancing the competitiveness of local products. Thus, this research not only contributes to improving service quality and customer satisfaction but also has the potential to drive economic growth and business development in Medan and its surrounding areas.